Side effects in 412 dogs from swimming in a chlorinated swimming pool - Nganvongpanit K. (2014)
This study reports the side effects in dogs from swimming in a chlorinated swimming pool. Data were collected from September 2008 until April 2012. A total of 412 dogs (male= 219 and female= 193), aged 38±30 months, served as the subjects. The dogs were divided into four groups based on the aims of swimming: entertainment (n= 152), weight reduction (n= 53), rehabilitation after orthopedic surgery (n= 81), and rehabilitation for muscle and joint disease (n= 126). The data were recorded for five separate swimming times. At first, some dogs (29.13%) showed overexcitement and/or fear, but this percentage decreased with increased swimming frequency. Some dogs (36.51%) were not able to swim, and required a trainer. The main side effects from the 1st swimming time included dry hair (20.63%), dry skin (18.93%), and abrasion wounds at the armpits (15.78%); these effects increased with increased frequency of swimming. Other side effects were red eyes (13.59%), otitis (6.31%), and a small number of respiratory problems (0.49%). In conclusion, data from this study can be used by veterinarians to inform pet owners about the potential side effects from swimming in chlorinated swimming pools.